Association of cartilage degeneration with four year weight gain – 3T MRI data from the Osteoarthritis Initiative. Issue 4 (April 2015) - Bucknor, M.D.; Nardo, L.; Joseph, G.B.; Alizai, H.; Srikhum, W.; Nevitt, M.C.; Lynch, J.A.; McCulloch, C.E.; Link, T.M.
Summary: Objective: To determine the effect of weight gain on progression of early knee morphologic abnormalities using magnetic resonance imaging (MRI) in a longitudinal study over 48 months. Design: We studied the right knee of 100 subjects from the Osteoarthritis Initiative (OAI), selecting subjects aged ≥45 with osteoarthritis (OA) risk factors who demonstrated weight gain (minimum 5% increase in body mass index, BMI, n = 50) or no change in weight (BMI change < 2%, n = 50), frequency matched for age, gender, and baseline BMI. Baseline and 48 month knee MRI studies were scored for lesions using a modified whole organ MRI score (WORMS). Logistic regression models were used to compare the differences between the two groups. Results: The odds of worsening maximum cartilage (11.3, 95%, CI 3.5–51.4) and meniscal WORMS (4.5, 95% CI 1.4–17.3) were significantly greater in the weight gain group compared to the no change group, in addition to the odds of worsening cartilage defects at the patella and average meniscal WORMS ( P  < 0.05). Odds of worsening average bone marrow edema pattern (BMEP) were significantly greater for the weight gain group compared to the no change cohort ( P  < 0.05). Conclusion: Our study demonstrated that weight gain is strongly associated with increased progression of cartilage degeneration in middle-aged individuals with risk factors for OA.